PRELIMINARY PHYTOCHEMICAL SCREENING OF VARIOUS EXTRACTS OF PUNICA GRANATUM PEEL, WHOLE FRUIT AND SEEDS - Bhandary, Satheesh Kumar; N., Suchetha Kumari; Bhat, Vadisha S; P., Sharmila K.; Bekal, Mahesh Prasad (Journal of Health and Allied Sciences NU, 2012)
Herbal medicines as the major remedy in traditional system of medicine have been used in medical practices since antiquity. In addition to its ancient historical uses, pomegranate is used in several systems of medicine for a variety of ailments. The objective of the present study was to investigate the presence of various phytochemicals from the ethanolic, aqueous and chloroform extracts of Punica granatum peel, whole fruit and seeds. The three different extracts from peel were found to contain Triterpenoids, Steroids, Glycosides, Flavonoids, Tannins, Carbohydrate & Vitamin C. The three different extracts from whole fruit were found to contain Triterpenoids, Steroids, Glycosides, Saponins, Alkaloids, Flavonoids, Tannins, Carbohydrate & Vitamin C. The three different extracts from seeds were found to contain Triterpenoids, Steroids, Glycosides, Saponins, Alkaloids, Tannins, Carbohydrate & Vitamin C.The generated data from the three different extracts of Punica granatum peel, whole fruit & seeds provided the basis for its wide uses in the traditional & folk medicines.
Keywords: Phytochemical; Punica granatum; Flavonoids